CityGolfNet a business intelligence system for City Golf Development Corporation - Goleetian, Allyson Sanchez; Zamora, Elvira A. (Quezon City University of the Philippines Diliman, 2009)
Project Title : CityGolfNet. Project Description : "CityGolfNet is a customer database with segmented arrangement that will give key decision-makers the up-to-date customer and market information to create meaningful strategic and tactical actions." Project Objectives : to create a system of collecting, housing, utilizing customer information for competitive advantage. Project duration : May 1, 2009 to September 30, 2009. Project result highlights : A customer database was the desired result for this project. The critical first step was the data gathering activity, followed by the process of housing and maintaining the information . The information life cycle was used as the model for developing the customer database of CityGolf Development Corporation. Key outputs were : 1. Customer Survey Form, 2. Customer Database. 3. Customer Database Analysis Reports. Project cost : 16,575.00 PHP, Proponents : Allyson S. Goleetian - UP-TMC. Sponsors : Raoul V. Lachica-CityGolf Development Corporation President, Raul U. Go Lee Tian - CityGolf Development Corporation Director of Finance & Leasing, Jose M. Saludares, Jr. - CityGolf Development Corporation Director of Administration & Operations. Date of Submission : 9 October 2009.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: CityGolfNet; City Golf Development Corporation; Business; Business intelligence system